2019
DOI: 10.1186/s12885-019-5676-3
|View full text |Cite
|
Sign up to set email alerts
|

PRIMMO study protocol: a phase II study combining PD-1 blockade, radiation and immunomodulation to tackle cervical and uterine cancer

Abstract: Background Immunotherapeutic approaches have revolutionized oncological practice but are less evaluated in gynecological malignancies. PD-1/PD-L1 blockade in gynecological cancers showed objective responses in 13–17% of patients. This could be due to immunosuppressive effects exerted by gynecological tumors on the microenvironment and an altered tumor vasculature. In other malignancies, combining checkpoint blockade with radiation delivers benefit that is believed to be due to the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Other humanized antibodies of checkpoint inhibitors targeting PD-1, such as atezolizumab, durvalumab, tremelimumab, ipilimumab and nivolumab, were also studied in EC with a POLE-ultramutated and MSI-hypermutated phenotype. A significant clinical response was observed in these clinical trials (111,(113)(114)(115)(116). These clinical trials involving immunotherapy for EC are available at https://clinicaltrials.gov, and are listed in Table III.…”
Section: Immunotherapy For Ecmentioning
confidence: 97%
See 1 more Smart Citation
“…Other humanized antibodies of checkpoint inhibitors targeting PD-1, such as atezolizumab, durvalumab, tremelimumab, ipilimumab and nivolumab, were also studied in EC with a POLE-ultramutated and MSI-hypermutated phenotype. A significant clinical response was observed in these clinical trials (111,(113)(114)(115)(116). These clinical trials involving immunotherapy for EC are available at https://clinicaltrials.gov, and are listed in Table III.…”
Section: Immunotherapy For Ecmentioning
confidence: 97%
“…These findings suggested that the assessment of an immune response rather than the molecular subtype may better predict a clinical response to immunotherapy (120,121). Nevertheless, as aforementioned, targeting the PD-1 signaling pathway has great potential in enhancing antitumor immune responses, as accumulating evidence demonstrates that antitumor functions are induced following PD-1 and PD-L1 engagement in cancer cells in vivo (50,(112)(113)(114)(115)(116)(117). These multifunctional PD-1 signaling pathways need to be made available for the treatment of additional types of cancer.…”
Section: Immunotherapy For Ecmentioning
confidence: 99%
“…The primary endpoint is the ORR at week 26 and the secondary endpoints include safety, ORR at week 26, best overall response, PFS, OS, and quality of life. This ongoing trial will end in 2022 [40]. Abbreviations: ORR; overall response rate, PFS; progression-free survival, DFS; disease-free survival, OS; overall survival.…”
Section: Combination Therapy Of Pd-1 Inhibitors With Chemotherapy Andmentioning
confidence: 99%
“…In the phase 2 PRIMMO Study, Tuyaerts et al are evaluating the antitumor efficacy of pembrolizumab in combination with radiotherapy and immunomodulation in UC patients [40]. Patients will receive pembrolizumab over 3 weeks for a total of 6 cycles, with radiation given on days 1, 3, and 5.…”
Section: Combination Therapy With Pd-1 Inhibitorsmentioning
confidence: 99%
“…Intra-tumoral injection of caerin 1.1 and 1.9 peptides in vaccinated TC-1 tumour bearing mice with PD-1 blockade modulates macrophage heterogeneity and the activation of CD8+ T cells in the tumour microenvironment cancers, including nearly 100% of cervical cancers 1 . Cervical cancers are the 3 rd most common cancer in women worldwide 2 . Moreover, high risk HPV infection, especially HPV16 infection, is related to a fraction of head and neck epithelial carcinoma in both developed and undeveloped countries 3 .…”
mentioning
confidence: 99%